Preparation method and application of anion / cation co-intercalation Ti3C2Tx electrode material

By modifying the organic molecules of the multi-electron conjugated macrocycle on the surface or between Ti3C2Tx and adjusting their energy band structure, a new energy storage mechanism for the co-intercalation of the lithium-ion battery is realized, which solves the problem of poor structural stability of graphite electrode materials and significantly improves the capacity and cycle stability of the lithium-ion battery.

CN119612516APending Publication Date: 2025-03-14BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411837187.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, graphite electrode materials limit the actual application of the battery due to poor structural stability, serious loss of lithium storage capacity and shortened cycle life.

Method used

By modifying the organic molecules of the multi-electron conjugated macrocycle on the surface or between Ti3C2Tx, adjusting the electron distribution in the surface interface area, triggering changes in the energy band structure, thereby realizing a new energy storage mechanism for anion/cation co-intercalation.

Benefits of technology

It achieves high-magnification capacity and excellent cycle stability of lithium-ion batteries, breaks through the theoretical specific capacity of traditional Ti3C2Tx, and significantly improves the energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612516A_ABST
    Figure CN119612516A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery electrode materials, and provides a preparation method and application of an anion / cation co-intercalation Ti3C2Tx electrode material. The preparation method of the anion / cation co-intercalation Ti3C2Tx electrode material provided by the invention comprises the following steps: etching a Ti3AlC2MAX phase through a fluorine-containing etching solution, collecting a few-layer Ti3C2Tx aqueous solution through ultrasound and centrifugation, and adjusting an energy band structure of Ti3C2Tx through organic molecule modification of a multi-electron conjugated macrocycle by utilizing a self-assembly method, so as to obtain the anion / cation co-intercalation Ti3C2Tx electrode material. The limitation that charging and discharging energy storage is realized by using single-type cations (such as Li < + >, Na < + >, K < + >, Ca < 2 + >, Mg < 2 + > and the like) as carriers to move in a rocking chair manner between positive and negative electrodes in the prior art is broken through, anions and cations in an electrolyte simultaneously participate in energy storage and release, and a novel anion / cation co-intercalation electrode material is developed. Therefore, the prepared anion / cation co-intercalation Ti3C2Tx electrode material breaks through the theoretical specific capacity (J.Am.Chem.Soc.2012, 134 and 16909) of 320mAh / g, and high rate capacity and excellent cycling stability are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery electrode materials, and in particular to an anion / cation co-intercalated Ti3C2T x Preparation methods and applications of electrode materials. Background Art

[0002] Lithium-ion batteries have been widely used in many fields such as portable electronic devices, road transportation, aerospace, and medical devices due to their high energy density, low self-discharge rate, no memory effect, and excellent cycle life. However, with the rapid growth of demand in the new energy market, more stringent requirements have been placed on the performance of lithium-ion batteries, including but not limited to improving power density, accelerating the charging process, and enhancing adaptability in a wide temperature range. As a key component of the battery, the performance of the electrode material largely determines the upper limit of the battery performance. Existing commercial graphite materials have obvious limitations: (1) The lithium insertion potential of graphite is very different from the lithium metal deposition potential. Larger polarization will reduce the lithium insertion potential of graphite to below 0V, resulting in lithium precipitation, causing loss of lithium source, increase in battery internal resistance and capacity decay; (2) Due to the slow desolvation process of graphite and the poor ion transfer kinetics in the formed solid electrolyte interface (SEI), the overpotential is high, which leads to a significant loss of lithium storage capacity. In severe cases, it may even cause the battery to be unable to charge; (3) The graphite layered structure is less stable. After a long period of charge and discharge cycles, the structure is prone to collapse, resulting in a serious decrease in specific capacity and a significant shortening of energy storage life. Especially when graphite stores anions, PF6 - Anions are inserted into graphite to form C 16 (PF6), whose theoretical capacity is limited to 140 mAh / g, and large-sized PF6 - Frequent intercalation and deintercalation can easily cause a sharp collapse of the graphite structure. Therefore, the above problems of graphite seriously restrict the practical application of commercial lithium-ion batteries. Therefore, the rational design of electrode materials with excellent energy storage properties is one of the keys to current lithium-ion battery research.

[0003] Ti3C2T x As the most studied and widely used MXene material, it has become a very competitive candidate for lithium-ion battery negative electrode materials due to its diverse surface chemical properties, unique two-dimensional layered structure, adjustable interlayer spacing, metal-like conductivity and adjustable nano-micro morphology. x It is an intercalation pseudocapacitor energy storage mechanism with fast energy storage characteristics, and is an ideal electrode material with both high energy density and high power density. x In the storage process, there is a general limitation of insufficient ion sources, that is, relying only on a single type of cation (such as Li +、Na + , K + , Ca 2+ Mg 2+ This intercalation pseudocapacitor storage mechanism based on the traditional "rocking chair" does not produce additional capacity contribution from the anions in the electrolyte. x The unique two-dimensional layered structure and high specific surface area advantages fully explore and utilize Ti3C2T x The additional anion storage potential inspires large-sized anions to be effectively embedded in their interlayer structure or adsorbed on the surface of their nanosheets, opening up a new path to significantly improve the energy density of lithium-ion batteries. Summary of the invention

[0004] In view of this, the present invention adopts the method of x The surface or interlayer modification of multi-electron conjugated macrocyclic organic molecules adjusts the electron distribution in the surface and interface regions, thereby affecting the band structure characteristics, causing changes in the band width, movement of the band position, or the introduction of new electronic states. To this end, we have achieved a goal of no longer relying on a single cation (such as Li + 、Na + , K + , Ca 2+ Mg 2+ As a new energy storage method for the charge carrier to move between the positive and negative electrodes, the anions and cations in the electrolyte are simultaneously involved in the storage and release of energy, and a new type of anion / cation co-intercalation electrode material is developed. x The electrode material has exceeded the theoretical specific capacity of 320 mAh / g (J.Am.Chem.Soc.2012,134,16909), achieving high rate capacity and excellent cycle stability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] 1) Preparation of few-layer Ti3C2T x Aqueous solution: The Ti3AlC2 MAX phase was etched with a mixture of concentrated HCl and LiF, and the multilayer Ti3C2T was obtained by washing with deionized water. x The aqueous solution was subjected to ultrasound and centrifugation to obtain a few-layer Ti3C2T x aqueous solution, and prepare Ti3C2T x The concentration of the aqueous solution is 1-5 mg / mL. The Ti3AlC2 MAX is one or more selected from three particle size specifications of 200 mesh, 400 mesh and 600 mesh.

[0007] 2) Prepare an organic molecule solution of a multi-electron conjugated macrocycle: the organic molecule is selected from the following: tetraaminophthalocyanine copper (II), tetracarboxylphthalocyanine cobalt (II), tetrasulfonic phthalocyanine zinc (II), sulfonated phthalocyanine cobalt (II), octahydroxyphthalocyanine cobalt (II), chlorinated phthalocyanine manganese (III), dichlorinated phthalocyanine tin (IV), simple metal phthalocyanine (Fe, Co, Ni, Cu, Zn, Mg, Sn, Pb, Mn, Al). The solvent used is selected from the following: deionized water, anhydrous ethanol, acetone, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran, chloroform, etc. The concentration of the multi-electron conjugated macrocycle organic molecule solution is 0.1-20 mg / mL. 3) Slowly drop the multi-electron conjugated macrocycle organic molecule solution onto the few-layer Ti3C2T x In aqueous solution, the multi-electron conjugated macrocyclic organic molecule solution and Ti3C2T x The volume ratio of the aqueous solution is (0.5-4):1, the reaction is condensed and refluxed for 3-18 hours, the reaction temperature is 40-100°C, and inert gas argon is passed for protection. After a period of reaction, a flocculent precipitate is obtained.

[0008] 4) The obtained flocculent precipitate was washed by centrifugation with deionized water, the centrifugal speed was controlled to be 3000-6000 r / min, the washing times were 1-5 times, and the anion / cation co-intercalated Ti3C2T x .

[0009] The original Ti3C2T x It can be prepared according to the following method: 1.0 g Ti3AlC2 MAX phase powder is slowly added to a mixed solution of 1.0 g LiF and 10 mL 9 mol / L HCl, and stirred in a constant temperature oil bath at 40 ° C for 36 h; the product obtained by the reaction is washed with deionized water several times until the solution pH is ≈ 7, and the lower precipitate is collected; ultrasonic dispersion treatment is performed under nitrogen protection for 1 h, and then centrifugation is performed at 3500 rpm for 1 h to obtain a few layers of dark green Ti3C2T x Aqueous solution, freeze-dried to obtain the original Ti3C2T x .

[0010] The anion / cation co-intercalation Ti3C2T x Electrode materials and their applications in lithium-ion battery electrode materials.

[0011] Compared with the prior art, the present invention has the following beneficial effects: the present invention creatively introduces a new energy storage mechanism of anion / cation co-intercalation, and cleverly uses multi-electron conjugated macrocyclic organic molecules to regulate Ti3C2T xThe band structure of lithium-ion batteries successfully triggers the co-intercalation behavior of cations and anions, thereby achieving a significant increase in energy storage capacity and significantly improving the cycle stability and rate performance of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The cobalt phthalocyanine modified Ti3C2T prepared in Example 1 of the present invention x Scanning electron microscope image;

[0013] Figure 2 The original Ti3C2T prepared in Comparative Example 1 of the present invention x Transmission electron microscopy images;

[0014] Figure 3 The cobalt phthalocyanine modified Ti3C2T prepared in Example 1 of the present invention x The original Ti3C2T prepared in Comparative Example 1 x Full spectrum of X-ray photoelectron spectroscopy (XPS);

[0015] Figure 4 The cobalt phthalocyanine modified Ti3C2T prepared in Example 1 of the present invention x The original Ti3C2T prepared by electrode and comparative example 1 x Cycling performance diagram of the electrode at a current density of 0.1 A / g;

[0016] Figure 5 The cobalt phthalocyanine modified Ti3C2T prepared in Example 1 of the present invention x The original Ti3C2T prepared by electrode and comparative example 1 x Rate performance diagram of the electrode;

[0017] Figure 6 The cobalt phthalocyanine modified Ti3C2T prepared in Example 1 of the present invention x Constant current charge-discharge curves of the electrode, and the corresponding ex situ X-ray diffraction (XRD) patterns;

[0018] Figure 7 The cobalt phthalocyanine modified Ti3C2T prepared in Example 1 of the present invention x XPS comparison of P 2p and Li1s of the electrode at 0.01V and 3.0V.

[0019] The technical solutions provided by the present invention are further explained clearly and completely below by means of specific embodiments, but they do not constitute a limitation to the present invention. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the following embodiments are only some specific embodiments of the present invention, rather than all embodiments.

[0021] Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the invention claimed, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the protection scope of the present invention.

[0022] Embodiment 1:

[0023] Preparation of Cobalt Phthalocyanine Modified Ti3C2T x Electrode materials, the steps are as follows:

[0024] (1) 1.0 g Ti3AlC2 MAX phase powder was slowly added into a mixed solution of 1.0 g LiF and 10 mL 9 mol / L HCl, and stirred in a constant temperature oil bath at 40 °C for 36 h. The product obtained by the reaction was washed with deionized water several times until the solution pH was ≈ 7, and the lower precipitate was collected. The product was subjected to ultrasonic dispersion treatment for 1 h under nitrogen protection, and then centrifuged at 3500 rpm for 1 h to obtain a few layers of dark green Ti3C2T x Aqueous solution.

[0025] (2) Prepare Ti3C2T with a concentration of 2 mg / mL x DMF solution.

[0026] (3) Prepare a 0.6 mg / mL DMF solution of cobalt phthalocyanine and add the DMF solution of cobalt phthalocyanine dropwise to the same volume of Ti3C2T x In DMF solution, condense and reflux at 90°C for 3h under argon protection to obtain flocculent precipitate, which is then placed at room temperature. The solution is then centrifuged and washed three times with deionized water at 3500r / min to remove excess multi-electron conjugated macrocyclic organic molecules, and then freeze-dried to obtain cobalt phthalocyanine-modified Ti3C2T x Electrode material.

[0027] (4) The prepared cobalt phthalocyanine-modified Ti3C2T x The electrode material was characterized, and its scanning electron microscope image is shown in Figure 1 , compared with the original Ti3C2T x ( Figure 2 ) transmission electron microscopy images, it has a three-dimensional porous network structure. Comparing the X-ray photoelectron spectroscopy (XPS) of the two Figure 3 ), Cobalt phthalocyanine modified Ti3C2T x The presence of Co and N elements indicates that cobalt phthalocyanine has been successfully modified to Ti3C2T x(5) The electrochemical properties of the material were tested using a CR2025 button cell. First, a slurry containing active material (70 wt%), conductive carbon black (20 wt%) and polyvinylidene fluoride (10 wt%) was coated on a copper foil and vacuum dried at 60 °C for 12 h. The active material loading on the electrode sheet was 1.0 to 1.4 mg / cm 2 The button cell was assembled in an argon-filled glove box, with a lithium metal sheet as the counter electrode, the above-mentioned electrode sheet as the working electrode, a 1 mol / L LiPF6 solution of ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) (volume ratio 1:1:1) as the electrolyte, and a polypropylene film (Celgard2400) as the separator.

[0028] (6) The lithium-ion button half-cell assembled above was subjected to electrochemical energy storage tests at a current density of 0.1 A / g and a voltage window of 0.01 to 3.0 V, including cycle stability ( Figure 4 ) and rate performance ( Figure 5 )test.

[0029] (7) The lithium ion button half-cell assembled above was subjected to 10 cycles of constant current charge and discharge at a current density of 0.1 A / g and a voltage window of 0.01 to 3.0 V. The ex-situ XRD ( Figure 6 ).Depend on Figure 6 It can be seen that when the battery is charged from 0.01V to 3.0V, in the voltage range of 0.01V to 2.0V, the Ti3C2T modified by cobalt phthalocyanine x The (002) diffraction peak gradually shifts to higher angles, indicating that Li + From Ti3C2T x The interlayer deintercalation reduces the interlayer distance; when charged to 2.0V, PF6 begins to be triggered - Insertion, so in the voltage range of 2.0V to 3.0V, the (002) diffraction peak shifts to a lower angle, indicating that the interlayer spacing is significantly expanded due to the insertion of large-sized anions. In the subsequent discharge process, the (002) diffraction peak shows an evolution trend opposite to that of the charging process, indicating that the anion / cation co-intercalation energy storage mechanism of this electrode material has excellent reversibility. In addition, by comparing the potentials of 0.01V and 3.0V, the cobalt phthalocyanine modified Ti3C2T x XPS graphs of P 2p and Li 1s of the material ( Figure 7 ) It can be seen that compared with the potential of 0.01 V, the Li element content at the potential of 3.0 V is significantly reduced, while the content of P element increases accordingly, which further verifies the energy storage mechanism of anion / cation co-intercalation.

[0030] Embodiment 2:

[0031] Preparation of Tetracarboxyphthalocyanine Cobalt(II) Modified Ti3C2T x Electrode materials, the steps are as follows:

[0032] (1) 1.0 g Ti3AlC2 MAX phase powder was slowly added into a mixed solution of 1.0 g LiF and 10 mL 9 mol / L HCl, and stirred in a constant temperature oil bath at 40 °C for 36 h. The product obtained by the reaction was washed with deionized water several times until the solution pH was ≈ 7, and the lower precipitate was collected. The product was subjected to ultrasonic dispersion treatment for 1 h under nitrogen protection, and then centrifuged at 3500 rpm for 1 h to obtain a few layers of dark green Ti3C2T x Aqueous solution.

[0033] (2) Preparation of 3 mg / mL Ti3C2T x Acetone solution.

[0034] (3) Prepare a 0.3 mg / mL acetone solution of tetracarboxyphthalocyanine cobalt (II) and add the acetone solution dropwise to the same volume of Ti3C2T x In acetone solution, condense and reflux at 50°C for 12h under argon protection to obtain flocculent precipitate, which is then placed at room temperature. The solution is then centrifuged and washed three times with deionized water at 4500r / min to remove excess multi-electron conjugated macrocyclic organic molecules, and then freeze-dried to obtain tetracarboxyphthalocyanine cobalt (II) modified Ti3C2T x Electrode material.

[0035] (4) The obtained tetracarboxyphthalocyanine cobalt (II) modified Ti3C2T x Electrode material, directly used as a lithium ion battery working electrode (replacing the cobalt phthalocyanine modified Ti3C2T x The process of preparing the lithium ion battery electrode is the same as that in Example 1.

[0036] Embodiment 3:

[0037] Preparation of Tetrasulfonic Acid Phthalocyanine Zinc(II) Modified Ti3C2T x Electrode materials, the steps are as follows:

[0038] (1) 1.0 g Ti3AlC2 MAX phase powder was slowly added into a mixed solution of 1.0 g LiF and 10 mL 9 mol / L HCl, and stirred in a constant temperature oil bath at 40 °C for 36 h. The product obtained by the reaction was washed with deionized water several times until the solution pH was ≈ 7, and the lower precipitate was collected. The product was subjected to ultrasonic dispersion treatment for 1 h under argon protection, and then centrifuged at 3500 rpm for 1 h to obtain a few layers of dark green Ti3C2T x Aqueous solution.

[0039] (2) Preparation of 4 mg / mL Ti3C2T x Ethanol solution.

[0040] (3) Prepare a 0.2 mg / mL ethanol solution of zinc phthalocyanine (II) tetrasulfonate, and add the ethanol solution of zinc phthalocyanine (II) tetrasulfonate dropwise to the same volume of Ti3C2T x The dispersion was condensed and refluxed at 80 °C for 6 h under argon protection to obtain a flocculent precipitate, which was then allowed to cool to room temperature. The precipitate was washed twice with deionized water at 5000 r / min to remove excess multi-electron conjugated macrocyclic organic molecules, and then freeze-dried to obtain tetrasulfonic acid phthalocyanine zinc (II) modified Ti3C2T x Electrode material.

[0041] (4) The obtained tetrasulfonic acid phthalocyanine zinc (II) modified Ti3C2T x Electrode material, directly used as a lithium ion battery working electrode (replacing the cobalt phthalocyanine modified Ti3C2T x The process of preparing the lithium ion battery electrode is the same as that in Example 1.

[0042] Embodiment 4:

[0043] Preparation of Tetraaminophthalocyanine Copper Modified Ti3C2T x Electrode materials, the steps are as follows:

[0044] (1) 1.0 g Ti3AlC2 MAX phase powder was slowly added into a mixed solution of 1.0 g LiF and 10 mL 9 mol / L HCl, and stirred in a constant temperature oil bath at 40 °C for 36 h. The product obtained by the reaction was washed with deionized water several times until the solution pH was ≈ 7, and the lower precipitate was collected. The product was subjected to ultrasonic dispersion treatment for 1 h under nitrogen protection, and then centrifuged at 3500 rpm for 1 h to obtain a few layers of dark green Ti3C2T x Aqueous solution.

[0045] (2) Preparation of 1 mg / mL Ti3C2T x DMF solution.

[0046] (3) Prepare a 10 mg / mL DMF solution of copper tetraaminophthalocyanine and add the DMF solution of copper tetraaminophthalocyanine dropwise to the same volume of Ti3C2T x The dispersion was condensed and refluxed at 45°C for 18 h under argon protection to obtain a flocculent precipitate, which was then allowed to cool to room temperature. The precipitate was washed once with deionized water at 6000 r / min to remove excess multi-electron conjugated macrocyclic organic molecules, and then freeze-dried to obtain tetraaminophthalocyanine copper modified Ti3C2T x Electrode material.

[0047] (4) The obtained tetraaminophthalocyanine copper modified Ti3C2T x Electrode material, directly used as a lithium ion battery working electrode (replacing the cobalt phthalocyanine modified Ti3C2T x The process of preparing the lithium ion battery electrode is the same as that in Example 1.

[0048] Embodiment 5:

[0049] Preparation of manganese(III) phthalocyanine chloride modified Ti3C2T x Electrode materials, the steps are as follows:

[0050] (1) 1.0 g Ti3AlC2 MAX phase powder was slowly added into a mixed solution of 1.0 g LiF and 20 mL 9 mol / L HCl, and stirred in a constant temperature oil bath at 40 °C for 36 h. The product obtained by the reaction was washed with deionized water several times until the pH of the solution was ≈ 7, and the lower precipitate was collected. The product was subjected to ultrasonic dispersion treatment for 1 h under nitrogen protection, and then centrifuged at 3500 rpm for 1 h to obtain a few layers of dark green Ti3C2T x Aqueous solution,

[0051] (2) Preparation of 4 mg / mL Ti3C2T x DMSO solution.

[0052] (3) First, prepare a 20 mg / mL phthalocyanine manganese (III) chloride DMSO solution, and add the phthalocyanine manganese (III) chloride DMSO solution dropwise to the same volume of Ti3C2T x The dispersion was condensed and refluxed at 80°C for 4 h under argon protection to obtain a flocculent precipitate, which was then allowed to cool to room temperature. The precipitate was then centrifuged and washed five times with deionized water at 3000 r / min to remove excess multi-electron conjugated macrocyclic organic molecules, and then freeze-dried to obtain chlorinated manganese phthalocyanine (III) modified Ti3C2T x Electrode material.

[0053] (4) The obtained phthalocyanine manganese (III) chloride modified Ti3C2T x Electrode material, directly used as a lithium ion battery working electrode (replacing the cobalt phthalocyanine modified Ti3C2T x The process of preparing the lithium ion battery electrode is the same as that in Example 1.

[0054] Comparative Example 1

[0055] 1.0 g Ti3AlC2 MAX phase powder was slowly added into a mixed solution of 1.0 g LiF and 10 mL 9 mol / L HCl, and stirred in a constant temperature oil bath at 40 °C for 36 h. The product obtained by the reaction was washed with deionized water several times until the solution pH was ≈ 7, and the lower precipitate was collected. Ultrasonic dispersion was performed under nitrogen protection for 1 h, and then centrifuged at 3500 rpm for 1 h to obtain a few layers of dark green Ti3C2T x Aqueous solution, freeze-dried to obtain the original Ti3C2T x Electrode material. The obtained original Ti3C2T x Electrode material, directly used as a lithium ion battery working electrode (replacing the cobalt phthalocyanine modified Ti3C2T x The process of preparing the lithium ion battery electrode is the same as that in Example 1.

[0056] The above description is only a specific embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent transformations made by the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. Anion / cation co-intercalation Ti3C2T x The method for preparing an electrode material comprises the following steps: (1) Ti3AlC2 MAX phase powder was slowly added into a mixed solution of concentrated HCl and LiF, stirred at 35-45°C for 24-36h, washed with deionized water, and obtained after ultrasonication and centrifugation. x Aqueous solution. (2) Prepare a solution of multi-electron conjugated macrocyclic organic molecules. (3) Slowly drop the multi-electron conjugated macrocyclic organic molecule solution in step (2) into the few-layer Ti3C2T x In the solution, flocculent precipitate is obtained after condensation and reflux reaction for a period of time. (4) The obtained flocculent precipitate was washed by centrifugation with deionized water and freeze-dried to obtain anion / cation co-intercalated Ti3C2T x .

2. The preparation method according to claim 1, characterized in that: In the step (1), Ti3AlC2 MAX is one or more selected from three particle size specifications of 200 mesh, 400 mesh and 600 mesh.

3. The preparation method according to claim 1, characterized in that: The few-layer Ti3C2T x The concentration of the aqueous solution is 1 to 5 mg / mL.

4. The preparation method according to claim 1, characterized in that: The multi-electron conjugated macrocyclic organic molecule in the step (2) includes but is not limited to any one of tetraaminophthalocyanine copper (II), tetracarboxylphthalocyanine cobalt (II), tetrasulfonate phthalocyanine zinc (II), sulfonated phthalocyanine cobalt (II), octahydroxyphthalocyanine cobalt (II), chlorinated phthalocyanine manganese (III), dichlorinated phthalocyanine tin (IV), and simple metal phthalocyanine (Fe, Co, Ni, Cu, Zn, Mg, Sn, Pb, Mn, Al).

5. The preparation method according to claim 1, characterized in that: The solvent of the multi-electron conjugated macrocyclic organic molecule solution in step (2) includes but is not limited to deionized water, anhydrous ethanol, acetone, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), tetrahydrofuran, chloroform, etc., and the concentration of the multi-electron conjugated macrocyclic organic molecule solution is 0.1 to 20 mg / mL.

6. The preparation method according to claim 1, characterized in that: In the step (3), the organic molecule solution of the multi-electron conjugated macrocycle and Ti3C2T x The volume ratio of the aqueous solution is (0.5~4):

1.

7. The preparation method according to claim 1, characterized in that: In the step (3), the condensation reflux time is 3 to 18 hours, the reaction temperature is 40 to 100° C., and the inert gas argon is used for protection.

8. The preparation method according to claim 1, characterized in that: In the step (4), the centrifugal speed is controlled to be 3000-6000 r / min, and the washing times are 1-5 times.

9. Anion / cation co-intercalated Ti3C2T prepared by the preparation method according to claim 1 x Application of electrode materials in lithium-ion batteries.